2022
DOI: 10.31943/jurnalrisalah.v8i3.326
|View full text |Cite
|
Sign up to set email alerts
|

Pendekatan Neurosains Dalam Strategi Pembelajaranuntuk Siswa Slow Learner

Abstract: Siswa slow learner adalah siswa berkebutuhan khusus yang mengalami keterlambatan dalam belajar. Penelitian ini bertujuan untuk mengetahui hubungan antara  neurosainsdalam strategi pembelajaran terhadap siswa slow learner dan metode pembelajaran terbaik bagi slow learner perspektif neurosains. Metode penelitian dilakukan dengan kajian literatur yang diperoleh dari google  scholardari tahun 2012-2022 dengan key word slow learner dan neurosains. Hasil pencarian diperoleh  sebanyak 34 artikel. Artikel-artikel ters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
1
7
0
3
Order By: Relevance
“…Another stduy was conducted sought to discover a neuroscience-based learning method to facilitate slow learner students in learning (Sumiati & Gumiandari, 2022). The study results suggested several game types that can facilitate slow learner students in learning, including activities involving music learning.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another stduy was conducted sought to discover a neuroscience-based learning method to facilitate slow learner students in learning (Sumiati & Gumiandari, 2022). The study results suggested several game types that can facilitate slow learner students in learning, including activities involving music learning.…”
Section: Resultsmentioning
confidence: 99%
“…The diversity of music learning methods found in the literature suggests that no single approach is suitable for all children in inclusive groupspreschool level (Sumartini et al, 2020;Sumiati & Gumiandari, 2022;Wadu et al, 2021). This emphasizes the importance of flexibility in the approach to music learning, taking into account the child's individual needs, interests and abilities.…”
Section: Music Learning Strategies In Early Childhood Inclusive Educa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Intelligence and well-being are the result of using the brain well [14]. This reason is what leads the science of brain neuroscience or neuroscience to be a science that can explain the relationship between the brain and soul and even the body of the human being, which means that it can be said that neuroscience is able to explain the important role of the human brain itself on all activities and activities carried out both consciously and unconsciously [15].…”
Section: Cerebellummentioning
confidence: 99%
“…Menurutnya, pendidik harus terlebih dahulu mengetahui dan memahami kinerja otak, dan memperhatikan kerja alamiah otak peserta didik dalam proses pembelajaran, pada akhirnya guru akan mampu menciptakan suasana belajar yang menghargai peserta didik serta menghindari terjadinya pemforsiran kerja otak peserta didik. Neurusains membantu guru untuk memahami kondisi siswa, misalnya siswa yang masuk ke dalam kategori slow learner, (Lihat juga Sumiati, 2022) dan meningkatkan keterampilan berfikir tingkat tinggi, (Rivalina, 2020) sehingga akhirnya guru dapat membantu siswa untuk mengoptimalisasikan fungsi otak dengan baik dan benar sehingga tujuan pembelajaran dapat tercapai dengan baik. (Dewi, dkk., 2018) Kajian ini akan menganalisis mengenai neurosains dan hubungannya dengan pembelajaran dan kesehatan spiritual, sehingga diharapkan mampu menambah wawasan dan pengetahuan sebagai aktivitis cendikia terkait relevansi ketiganya ini.…”
unclassified